III Luso-Brazilian Congress of Physical Education (Fiep Bulletin - online, 2015)
Luanda - Angola-Portugal - From 20th to July 30th 1966. I- III Luso-Brazilian Congress of Physical Education is organized in Angola Province by the Ministry of Overseas Territories in order to further strengthen the cultural and emotional ties that unite Brazil and Portugal. Will take place in Luanda